(untitled) (Journal of the College of Basic Education, 2025)
Islam has been accused of various charges, including that it spread by the sword and through Islamic conquests that forced the inhabitants of the countries it conquered to embrace the Islamic religion. The research is a response to that suspicion raised by some orientalists and those who were influenced by them and followed their path from the superficial-minded Muslims, by presenting historical facts about the spread of the Islamic religion in the far east of the earth due to trade in which the merchants carried the teachings and morals of the true Islamic religion, until the largest Islamic countries in terms of population today are from that region, and this is a refutation of the opinions that accused Islam of spreading by the sword.